Evaluation of selected cocoa (Theobroma cacao L.) hybrids bred for quality - Ajmal P M (Department of Plantation Crops and Spices,College of Horticulture, 2016)
Cocoa (Theobroma cacao L.) is an important beverage crop belonging to the family Malvaceae. The most important economic part of cocoa is the optimally fermented and dried beans, which is the only source of chocolate flavour. Consumers have shown an increased interest for high quality dark chocolate containing a higher percentage of cocoa. Therefore, the quality of cocoa beans has a great importance while considering the market value. The genetic makeup of an individual cocoa genotype influences flavour, quality and intensity of chocolate.Cocoa is mainly classified into three types, namely Criollo, Forastero and Trinitario. The Criollo types provide fine flavour chocolate. At present fine cocoa production is very less due to the low productivity and disease susceptibility. More than 80 percent of cocoa plantations are established with Forastero types considering its higher yield and tolerance to pests and diseases. Due to increase in demand for fine cocoa in the market, it is important to have genotypes where quality is combined with hardiness. Hence, hybridization programme was initiated at Cocoa Research Center (CRC), KAU, Vellanikkara during 2004 for the development of varieties with beans of superior quality without sacrificing the yield and disease tolerance. Parental lines identified as having superior quality were crossed with high yielders with disease tolerance. Thirty hybrid progenies derived from the crosses were selected for the present study based on initial performance. These hybrids were subjected to morphological, biochemical, quality parameters and sensory evaluation. The morphological evaluation based on eight qualitative and seventeen quantitative characters was carried out using the descriptor developed by Bekele and Butler (2000). Biochemical and quality parameters were estimated following standard procedures and organoleptic evaluation was carried out based on nine point hedonic scale. Variability was observed among the hybrids for all the qualitative characters evaluated. Qualitative Criollo characters were observed among the hybrids indicating the transfer of Criollo characters from the parents to the progenies. Variations expressed by the hybrids in terms of pod and bean quantitative characters were also significant, indicating their heterogeneity. Analysis of pod and bean characters revealed that the hybrids; Hyb.10, Hyb.21 and Hyb.11 expressed higher values with respect to pod weight (685g), total wet bean weight (185.72g) and dry weight of single bean (1.48g) respectively. The highest values for yield, dry matter recovery and pod index recorded in Hyb.6 (111 pods/ tree/ year), Hyb.5 (81.2%) and Hyb.11 (15) respectively. Analysis of biochemical and quality parameters revealed that the fat content ranged from 39% in Hyb.28 to 56.5% in Hyb.17, total phenol content ranged from 2.95% in Hyb.27 to 5.45% in Hyb.15, protein content ranged from 12.15% in Hyb.27 to 17.4% in Hyb.17 and the alkaloid content ranged from 2.65% in Hyb.4 to 4.2% in Hyb.26. The highest values for TSS, fermentation index and fermentation recovery observed in Hyb.10 (22° brix), Hyb.17 (78%) and Hyb.6 (41.2%) respectively.Sensory evaluation of the chocolates prepared from the selected hybrids revealed that hybrids; Hyb.6, Hyb.7 and Hyb.10 scored high rank with respect to overall acceptability. Among the thirty hybrids evaluated, hybrids; Hyb.6, Hyb.7, Hyb.11 and Hyb.17 were found to possess with both Criollo and Forastero characters along with premium quality chocolates. Therefore, these hybrids can be further evaluated in comparative yield trial for variety release. Hybrids with superior Criollo characters (Hyb.12, Hyb.15 and Hyb.18) can be further used in breeding programmes.